Çizilmiş Cironun Hukukî Sonuçları - Çamoğlu, Ersin (Ankara Üniversitesi, 2019)
Ciroyu ancak maddi hukuka göre hak sahibi olan ciranta çizebilir (iptal edebilir). Ciranta bu işlemi kural olarak kendi cirosu üzerinde yapar. Bir cirantanın başka ciroları çizmesi (iptal etmesi) sadece müracaat haklarının kullanılması aşamasında TK 727(2) maddesinin izin verdiği sadeleştirme işleminde mümkündür. Ciranta çizme (iptal) işlemini HMK 207 madde uyarınca bu işlemden dönme veya işlemi değiştirme iradesini belirterek ve parafıyla onaylayarak yapmalıdır. Ciranta bu suretle ciroyu tamamen veya kısmen iptal edebilir. Cironun karalanması, silinmesi, kazınması vb. yoluyla yapılan atipik çizmeler (fiili iptaller) ise hak sahibinin imzası ile onaylanmadığı sürece geçersizdir; ciro zincirinde kopukluk yaratırlar. Cironun yetkili olmayan kişilerce çizilmesi, resmi senette tahrifat ya da sahtecilik suçunu oluşturur (TCK 204, 210).

Only the endorser who is the right holder pursuant to substantive law can cross (cancel) the endorsement. In principle, endorser executes this transaction over his/ her own endorsement. Crossing (cancellation) of other endorsements by the endorser is possible only for the simplification transactions, permitted by Art. 272(2) of Commercial Code, in the course of the exercise of application rights. The endorser must execute this crossing (cancellation) transaction by indicating the will of avoidance or alteration of the transaction according to Art. 207 of Code of Civil Procedure, and by approving with his/her initials. By this way, the endorser can cancel the endorsement completely or partially. Atypical crossings (if they are actual cancellations) made through crossing out, erasure or scratch of the endorsement are invalid as long as they are not approved by the right holder’s signature; they create a break in the chain of endorsements. The crossing of endorsement by unauthorized persons constitutes offenses of forgery or falsification of official documents (Art. 204 and 206 of Turkish Criminal Code).
Keywords: Çizilmiş Ciro; Cirodan Dönme; Haklı (Yasal) Çizmeler; Atipik Çizmeler; Ciro Zincirinde Sadeleştirme; Crossed Endorsement; Avoidance of Endorsement; Lawful (Legal) Crossings; Atypical Crossings; Simplification of Endorsement Chain